Anti-β2 Glycoprotein I Antibodies Cause Inflammation and Recruit Dendritic Cells in Platelet Clearance - Bondanza, Attilio; Manfredi, Angelo A.; Zimmermann, Valérie S.; Iannacone, Matteo; Tincani, Angela; Balestrieri, Genesio; Sabbadini, Maria Grazia; Querini, Patrizia Rovere (Thrombosis and Haemostasis, 2001)
Scavenger phagocytes are mostly responsible for the in vivo clearance of activated or senescent platelets. In contrast to other particulate substrates, the phagocytosis of platelets does not incite pro-inflammatory responses in vivo. This study assessed the contribution of macrophages and dendritic cells (DCs) to the clearance of activated platelets. Furthermore, we verified whether antibodies against the β2 Glycoprotein I (β2GPI), which bind to activated platelets, influence the phenomenon. DCs did not per se internalise activated platelets. In contrast, macrophages efficiently phagocytosed platelets. In agreement with the uneventful nature of the clearance of platelets in vivo, phagocytosing macrophages did not release IL-1β, TNF-α or IL-10. β2GPI bound to activated platelets and was required for their recognition by anti-ββ2GPI antibodies. DCs internalised platelets opsonised by anti-ββ2GPI antibodies. The phagocytosis of opsonised platelets determined the release of TNF-α and IL-1β by DCs and macrophages. Phagocytosing macrophages, but not DCs, secreted the antiinflammatory cytokine IL-1β0. We conclude that anti-ββ2GPI antibodies cause inflammation during platelet clearance and shuttle platelet antigens to antigen presenting DCs.
Keywords: Antiphospholipid antibodies; platelets; macrophages; dendritic cells; tumor necrosis factor-α